PELAKSANAAN KURIKULUM JSIT DALAM KURIKULUM MERDEKA UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI SMA SWASTA ISLAM TERPADU AL IZZAH - Purba, Fauzul Azmi; Mahariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Integrated Islamic School Network (JSIT) Curriculum in collaboration with the Merdeka Curriculum in improving the quality of education at Al Izzah Integrated Islamic Private High School. The study used qualitative methods with observation, interviews, and documentation techniques with the principal, vice principal for curriculum, and teachers. The results showed that the curriculum implementation at Al Izzah IT High School was carried out through three main aspects: planning, implementation, and assessment. In the planning stage, teachers are required to develop learning tools that integrate the learning outcomes of the Merdeka Curriculum with the Islamic values contained in the JSIT Curriculum. In the implementation stage, learning begins with habituation of worship such as prayer, reading Al-Matsurat, and linking material to verses of the Qur’an and hadith. In addition, the school also develops flagship programs such as Tahfidz and Tahsin Al-Qur’an, mentoring and extracurricular sunnah (archery). In the assessment stage, teachers assess students holistically covering academic aspects, attitudes, discipline, and religiosity. The implementation of this curriculum has been proven to be able to improve the academic quality, Islamic character, and social competence of students so that the school’s vision, namely to form an Islamic, superior, and globally-minded generation, can be achieved.